The German Dunkelfeld Project: A Pilot Study to Prevent Child Sexual Abuse and the Use of Child Abusive Images. (1st February 2015) - Beier, Klaus M.; Grundmann, Dorit; Kuhle, Laura F.; Scherner, Gerold; Konrad, Anna; Amelung, Till
Abstract: Introduction: Sexual interest toward prepubescents and pubescents (pedophilia and hebephilia) constitutes a major risk factor for child sexual abuse (CSA) and viewing of child abusive images, i.e., child pornography offenses (CPO). Most child sexual exploitation involving CSA and CPO are undetected and unprosecuted in the "Dunkelfeld" (German: "dark field"). Aim: This study assesses a treatment program to enhance behavioral control and reduce associated dynamic risk factors (DRF) in self‐motivated pedophiles/hebephiles in the Dunkelfeld. Methods: Between 2005 and 2011, 319 undetected help‐seeking pedophiles and hebephiles expressed interest in taking part in an anonymous and confidential 1‐year‐treatment program using broad cognitive behavioral methodology in the Prevention Project Dunkelfeld. Therapy was assessed using nonrandomized waiting list control design (n = 53 treated group [TG]; n = 22 untreated control group [CG]). Main Outcome Measures: Self‐reported pre‐/posttreatment DRF changes were assessed and compared with CG. Offending behavior characteristics were also assessed via self‐reporting. Results: No pre‐/postassessment changes occurred in the control group. Emotional deficits and offense‐supportive cognitions decreased in the TG; posttherapy sexual self‐regulation increased. Treatment‐related changes were distributed unequally across offender groups. None of the offending behavior reported for the TG was identified as such by the legal authorities. However, five of 25 CSA offenders and 29 of 32 CPO offenders reported ongoing behaviors under therapy. Conclusions: Therapy for pedophiles/hebephiles in the Dunkelfeld can alter child sexual offending DRF and reduce‐related behaviors. Unidentified, unlawful child sexual exploitative behaviors are more prevalent in this population than in officially reported recidivism. Further research into factors predictive of problematic sexual behaviors in the Dunkelfeld is warranted.